CISSP in 21 days boost your confidence and get the competitive edge you need to crack the exam in just 21 days! - Srinivasan, M. L. (Community experience distilled, 2016)
Certified Information Systems Security Professional (CISSP) is an internationally recognized and coveted qualification. This simple yet informative book provides concise explanations of important concepts in all 10 domains of the CISSP Common Body of Knowledge (CBK)